A cell surface molecule involved in aggregation of embryonic liver cells. - Bertolotti, R (1980)
Aggragation of chicken enbryo hepatocytes can be inhibited by Fab' fragments of antibodies prepared against the cells. An aqueous extract of liver cell membranes contained antigens that neutralized the adhesion-blocking properties of the Fab' fragments. This neutralization activity was associated with a polypeptide of Mr68,000 in NaDodSO4; the polypeptide was distinct from serum albumin. Specific antibodies prepared against the 80-fold purified active fraction inhibited liver cell adhesion and immunoprecipitated the 68,000 Mr polypeptide from active fractions as well as from a detergent extract of liver cell membranes. In hepatocyte cultures, Fab' fragments of antibodies against the liver molecule prevented both colony formation and appearance of histotypic patterns. Liver cell adhesion was compared at the cellular and molecular levels to that of embryonic neural retina cells. Antibodies against the cell adhesion molecule from neural tissue inhibited retinal but not liver cell aggregation; conversely, antibodies against the liver polypeptide inhibited liver but not retinal cell aggregation. By means of antibody absorption and immunoprecipitation, it was confirmed that the two cell adhesion molecules are antigenically unrelated.